The case for greater project-level transparency of the UN's development work - Max-Otto Baumann (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
There is a case to be made for greater transparency of the United Nations' (UN) development work at the country level. Transparency can, in the simplest terms, be defined as the quality of being open to public scrutiny. Despite improvements in recent years, UN organisations still only partially meet this standard. Only the UN Development Programme (UNDP) and, with limitations, the World Food Programme (WFP) systematically publish basic project parameters such as project documents, funding data and evaluations. Others do not even publish project lists. Only the UN Children's Fund (UNICEF) publishes evaluations - a key source on performance - in an easily accessible way next to programme or project information. Lack of project transparency constitutes not only a failure to operate openly in an exemplary way, as should be expected of the UN as a public institution with aspirations to play a leadership role in global development. It also undermines in very practical ways the development purposes that UN organisations were set up for: It reduces their accountability to the stakeholders they serve, including executive boards and local actors; it hampers the coordination of aid activities across and beyond the UN; and it undermines the learning from both successes and failures. In principle, the UN and its development organisations (which in many cases also provide humanitarian assistance) have fully embraced transparency. All nine of the UN's funds and programmes had joined the International Aid Transparency Index (IATI) by 2019; four of them have also set up their own transparency portals that provide information on country-level work. The UN Secretary-General has made greater transparency and accountability key priorities of his ongoing reform efforts to strengthen the UN development system (UNDS) and win the trust of governments, both as hosts and donors. However, existing transparency arrangements in many cases fall short - either through their design or implementation - in creating a meaningful degree of transparency at the operational level of projects. It appears that both UN organisations and member states, for whom transparency comes with (perceived) downsides, have accepted improvements in project transparency in recent years as a kind of mission accomplished. Ongoing reforms focus on the level of country programmes, where they promise greater transparency on financial allocation patterns and aggregated results. This focus on programme-level transparency should be complemented by full transparency on how the UN works and achieves results at the level of projects. The following actions are recommended: Member states should request full project-level transparency in the UN General Assembly and the executive boards of UN development organisations. Member states should, in the executive boards, review agency-specific rules and mechanisms regarding transparency and monitor compliance. The UN Sustainable Development Group (UNSDG) should ensure that a system-wide UN transparency standard exists.
Keywords: 330